What are the barriers and prospects for integrating environmental sustainability into the curriculum? - Rorke, Joshua (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2017)
This study attempts to investigate the extent to which environmental sustainability has been integrated into the curriculum of the Humanities Faculty at Rhodes University as well as the barriers and prospects for further integration. This thesis argues that the integration of environmental sustainability has been very limited. The three main components of environmental sustainability, namely environmental content, interdisciplinarity and participatory curriculum formation, are all lacking in most departments' curricula. This is despite all departments' affirmation that environmental issues are among the most critical problems the world faces today. Most of the departments are arguably only paying lip-service to environmental issues while making little to no effort toward integrating the environment into their curriculum. A lack of space in the curriculum is a frequently suggested barrier to introducing environmental sustainability into a course. However, this thesis argues that the environmentally conscious transformation of a curriculum cannot be achieved simply by adding content to the existing syllabus, but requires a restructuring of the curriculum itself. Many of the other barriers found by this study can be overcome through sufficient will on the part of departments to change their curricula. However, generating this will is difficult, as students are not ostensibly interested in environmental concerns. It is then incumbent on the lecturers themselves to educate the students on critical environmental issues, as well as on students to urge their lecturers to bring about change.
Keywords: Uncatalogued